A QUALITATIVE STUDY: HOSPITAL PATIENT COMPLAINT MANAGEMENT - Siti Kurnia Widi Hastuti; Nikita Cahyani Baginda; Selly Apri anda (Indonesian Journal of Health Administration, 2022)
Background: Complaint management is vital for hospitals as patient complaints can be used to advance the quality of health services provided. Aims: This study analyzed patient complaint management at an X government hospital in Yogyakarta. Methods: The research used a descriptive-qualitative method and phenomenology, which was carried out through in-depth interviews, observation, and document review. It involved the head of the legal and public relations department, the head of the public relations sub-division, two staff of the legal and public relations department,      two officers to outpatient and inpatient units, and two patients. This study used purposive sampling to select the samples. Data analysis referred to was from the concept of Miles and Huberman, which consists of data reduction, display, and verification. The accuracy of all data was checked using a triangulation method. Results: The hospital followed the patient complaint management procedures. Providing complaint reporting platforms is required to lodge patient complaints to the hospital. Moreover, the suggestion box should be managed properly, and thus the complaints on the box can be managed promptly. Conclusion: Overall, patient complaint management at the hospital has been carried out well and followed the standard operating procedures (SOP).